2020
DOI: 10.3390/polym12010087
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Surface Wettability of PET Polymer upon Treatment with an Atmospheric-Pressure Plasma Jet

Abstract: A useful technique for pre-treatment of polymers for improved biocompatibility is surface activation. A method for achieving optimal wettability at a minimal thermal load and unwanted modifications of the polymer properties is elaborated in this paper. Samples of polyethylene terephthalate polymer were exposed to an atmospheric-pressure plasma jet created by a high-impedance low-frequency discharge in wet argon. Different treatment times and distances from the end of the glowing discharge enabled detailed inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…In the case of a rapid activation, a very sharp interphase between the activated and the unaffected surface was observed and explained by the peculiarities of high-impedance discharges sustained in Ar with the presence of impurities from water vapor. The results obtained by X-ray photoelectron spectroscopy confirmed that the activation was a consequence of functionalization with oxygen functional groups [33].…”
supporting
confidence: 53%
“…In the case of a rapid activation, a very sharp interphase between the activated and the unaffected surface was observed and explained by the peculiarities of high-impedance discharges sustained in Ar with the presence of impurities from water vapor. The results obtained by X-ray photoelectron spectroscopy confirmed that the activation was a consequence of functionalization with oxygen functional groups [33].…”
supporting
confidence: 53%
“…Several authors have already reported results on the surface finish of the polymers using APPJ [5][6][7][8][9], and few presented surface mapping or line analyses of induced modification versus the discharge parameters [4,11,12,21]. Recently, we reported systematic research on the surface finish of the polyethylene terephthalate polymer [10]. We found enhanced wettability of this material at prolonged treatment times.…”
Section: Introductionmentioning
confidence: 73%
“…The droplets were deposited every 5 mm in such a way that the whole surface was mapped. More details about measurements and experimental setup can be found in our previous paper [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of techniques reported the reduction of C–C and C–H bindings from the inclusion of oxygen and nitrogen in the surface [ 3 , 4 , 5 , 23 ]. It is also reported that the introduction of an inert gas facilitates the formation of plasma and promotes the dissociation of hydrocarbons [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%